Analysis of Host-Specific Differentiation of Puccinia striiformis in the South and North-West of the European Part of Russia - Elena Gultyaeva (MDPI AG, 2021)
Yellow (stripe) rust, caused by Puccinia striiformis Westend. (Pst), is a major disease of cereals worldwide. We studied Pst virulence phenotypes on Triticum aestivum, Triticum durum, and triticale in three geographically distant regions of the European part of Russia (Dagestan and Krasnodar in North Caucasus, and Northwest) with different climate and environmental conditions. Based on the set of twenty differential lines, a relatively high level of population diversity was determined with 67 different Pst pathotypes identified among 141 isolates. Only seven pathotypes were shared by at least two hosts or occurred in the different regions. No significant differentiation was found between regional Pst collections of pathotypes either from T. aestivum or from T. durum. A set of Pst pathotypes from triticale was subdivided into two groups. One of them was indistinguishable from most durum and common wheat pathotypes, whereas the second group differed greatly from all other pathotypes. All sampled Pst isolates were avirulent on lines with Yr5, Yr10, Yr15, and Yr24 genes. Significant variation in virulence frequency among all Pst collections was observed on lines containing Yr1, Yr3, Yr17, Yr27, and YrSp genes and cvs Strubes Dickkopf, Carstens V, and Nord Desprez. Relationships between Russian regional collections of Pst from wheat did not conform to those for P. triticina.